Biology Learning Result of X Grade Senior High School Students through the Implementation of PBL combined with Flipped Classroom - Wardani, Jhera Cesaria; Agustina, Putri (Universitas Muhammadiyah Surakarta, 2024)
Flipped classroom is a learning method that allows students to learn the material in advance at home according to the assignments given by the teacher. The intent of this study is to discover out whether the flipped classroom-based PBL learning approach impacts biology learning outcomes in class X SMA Negeri 4 Surakarta. This study conducted quasi-experimental research, using a post-test only control group approach. The population comes from class X students of SMA Negeri 4 Surakarta with the sample comprised of two classes generated using the cluster random sampling method, that is, phase E3 as the experimental class and phase E1 as the control class. Assessments, survey questionnaires, and observes are some of the data gathering procedures applied. Data analysis employs statistical techniques that are both descriptive and inference-based. The research results show that 1) The average cognitive learning results in the experimental class were 76.61, whereas the control group had 63.02. 2) The average affective test scores in the experimental class were 72.73, alongside the control class had 67.91. 3) The average results of psychomotor learning section in the experimental group had 67,36 along with the result from control group had 61,11. In accordance with the research findings, it can be inferred that flipped-based PBL learning classrooms influence biology learning outcomes in biotechnology material. Even though it has advantages, implementing flipped classroom learning can also potentially cause several obstacles.